2021
DOI: 10.1037/pspp0000357
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling an exclusive link: Predicting behavior with personality, situation perception, and affect in a preregistered experience sampling study.

Abstract: Affect and situation perception are intertwined in any given situation, but the extent to which both predict behavior jointly and uniquely has not yet been systematically examined so far. Using two studies with experience sampling methodology (ESM), we examine how trait-like variables (Big Six, trait affect, general situation experience) and state-like variables (momentary affect, happiness, and situation perception) account for variance in self-reported behavioral states of the Big Six. In Study 1, we re-anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
67
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 130 publications
(316 reference statements)
12
67
1
Order By: Relevance
“…Our findings suggest that although we did observe several cross-rater effects, the presence of same-source bias (of both self-and other-ratings) may indeed be highly likely in experience sampling studies (see, e.g., Table 5). While many researchers (e.g., Horstmann et al, 2020) have raised awareness to such biases, our study is among the first to make this potential issue actually visible. However, an open question remains whether this is an actual bias because of the rating source, or whether this pattern may in fact reflect meaningful variance.…”
Section: Merits and Implicationsmentioning
confidence: 87%
See 3 more Smart Citations
“…Our findings suggest that although we did observe several cross-rater effects, the presence of same-source bias (of both self-and other-ratings) may indeed be highly likely in experience sampling studies (see, e.g., Table 5). While many researchers (e.g., Horstmann et al, 2020) have raised awareness to such biases, our study is among the first to make this potential issue actually visible. However, an open question remains whether this is an actual bias because of the rating source, or whether this pattern may in fact reflect meaningful variance.…”
Section: Merits and Implicationsmentioning
confidence: 87%
“…This way, this particular setting allows for a fundamental methodological improvement in research on person-situation dynamics. Second, extending research on person-situation dynamics-which is typically carried out with student samples (e.g., Horstmann et al, 2020;Rauthmann et al, 2015c;Sherman et al, 2015)-to an applied context may also significantly advance our knowledge on how such dynamics between persons and situations present themselves in an education setting. Such findings may be especially relevant for researchers on an applied level.…”
Section: Person-situation Dynamics In An Education Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifth and finally, recent studies have examined the extent to which within-person fluctuations in both situational perception and personality states may overlap with fluctuations in affect (Horstmann et al, 2020;Wilson et al, 2017). Wilson et al (2017), for example, demonstrated that situation variables predicted variance in personality states after accounting for fluctuations in affect, although only to a limited extent.…”
Section: Limitations and Prospectsmentioning
confidence: 99%